In vitro bioactivities and phytochemical profile of various parts of the strawberry (Fragaria × ananassa var. Amaou). (March 2015) - Zhu, Qinchang; Nakagawa, Toshinori; Kishikawa, Asuka; Ohnuki, Koichiro; Shimizu, Kuniyoshi
Highlights: Besides antioxidant activity, three other bioactivities were investigated. The fruits as well as nine other parts of strawberry were comparatively studied. The phytochemical profiles of each parts of strawberry were determined. The strawberry fruits possess potential anti-obesity and skin-lightening effects. The parts of crown, stolon leaf and flower showed extraordinary activities. Abstract: The in vitro antioxidant, anti-obesity, anti-allergy and skin-lightening effects of extracts from strawberry fruits (ripe and unripe) and nine other plant parts of Amaou strawberry ( Fragaria   ×   ananassa var. Amaou ) were comparatively investigated by using the antioxidant assay and inhibition assays of lipase, adipocyte differentiation, β-hexosaminidase release, melanogenesis and tyrosinase. Their total phenolic content and the main phenolic compounds were also determined. The ripe strawberry fruits were found to possess potential anti-obesity and skin-lightening effects. The ethanol extracts from unripe strawberry fruits and several other parts like the crown, stolon leaf and flower showed more strong activities in the bioactivity assays conducted. The phytochemical profile varied among extracts from various parts of the plant. Ellagic acid was found in every part of the strawberry plant except the root. Our study provides valuable evidence that strawberry fruit is a food with potential anti-obesity and skin-lightening functions. The findings also support that several inedible parts of the strawberry plant have great potential to be used as the ingredients of functional food products.